Oligochaeta (Annelida) do Instituto Nacional de Pesquisas da Amazônia - Righi, Gilberto; Ayres, Ione; Bittencourt, Elizabeth C. R. (Acta Amazonica, 1978)
From the Brazilian Amazonia 25 species of Oligochaeta were studied for their anatomy and systematics. They are distributed onto 16 genera and 8 families as follows. Haplotaxidae: Tiguassu reginae gen. n., sp. n.; Enchytraeidae: Marionina patua sp. n.; Alluroididae: Brinkhurstia americanus (Brinkhurst, 1964); Glosos-colecidae: Atatina gatesi, sp. n., Amazo atroaris, sp. n.; A. xecatu, sp. n., Meroscolex eudoxiae, sp. n.; Diacheta juli, sp. n., Holoscolex caramuru Righi, 1975, H. nemorosus tacoa, subsp. n., Glossodrilus (G.) schubarti, sp. n.; Sparganophilidae: Areco reco, gen. n., sp. n.; Ocnerodrilidae: Eukerria guamais Righi, 1971, Haplodrilus (Hi) tagua, sp. n., Dariodrilus ferrarius, gen. n., sp. n., Exisdrilus rarus, gen. n., sp. n.; Acanthodrilidae : Wegeneriella divergens itapecu, subsp. n.; Wi. tocaya, sp. n.; Octochaetidae : Dichogaster affinis (Michaelsen, 1890), D. bolaui bolaui (Michaelsen, 1891), D. modigliani (Rosa, 1896), D. saliens (Beddard, 1892), D. andina evae, subsp. n., D. ibaia, sp. n., D. badajos, sp. n.